Incorporating Artificial Intelligence and MALL Strategies in EFL Classrooms: Interactive Pedagogical Praxis - Alam, Sohaib; Ahmad, Farhan; Nickolaeva Biryukova, Yulia (Journal of Education Culture and Society, 2024)
Aim. Pedagogical practices in English as a Foreign Language (EFL) classrooms are facing numerous challenges, experiencing artificial intelligence coming into classrooms across the globe. The present study aims to decipher the challenges pedagogues face in tackling the EFL classroom situation. The research explores the problems teachers face after introducing the artificial intelligence revolution in academia.Methods. The present study is devoted to the collection of responses from EFL teachers teaching language at university level. The study uses the quantitative method using a questionnaire to elicit responses from thirty eight (38) teachers teaching in different countries of the Middle East, especially at undergraduate level EFL students emphasising skills in the English language.Results. The findings reveal that pedagogues are still in a dilemma as to whether to allow or restrict students use of artificial intelligence (AI) tools for language learning tasks.Conclusion. The respondents reveal that the reason is insufficient literature on what and how to use AI tools effectively for language learning purposes.Cognitive Value. The present study intends to investigate the issues and challenges that language classrooms are using to integrate AI tools for teachers and also tries to provide a roadmap of strategies that can be utilised to teach English language using mobile aided language learning (MALL) strategies. The present study findings can be beneficial for academia to decide, think, and enact students learning outcomes by using AI tools and MALL strategies for better future action plans in classroom pedagogy.